Risk Factors and Neurologic Outcomes Associated With Resuscitation in the Pediatric Intensive Care Unit - Lee, En-Pei; Chan, Oi-Wa; Lin, Jainn-Jim; Hsia, Shao-Hsuan; Wu, Han-Ping (Frontiers in Pediatrics, 2022)
In the pediatric intensive care unit (PICU), cardiac arrest (CA) is rare but results in high rates of morbidity and mortality. A retrospective chart review of 223 patients who suffered from in-PICU CA was analyzed from January 2017 to December 2020. Outcomes at discharge were evaluated using pediatric cerebral performance category (PCPC). Return of spontaneous circulation was attained by 167 (74.8%) patients. In total, only 58 (25%) patients survived to hospital discharge, and 49 (21.9%) of the cohort had good neurologic outcomes. Based on multivariate logistic regression analysis, vasoactive–inotropic drug usage before CA, previous PCPC scale >2, underlying hemato-oncologic disease, and total time of CPR were risk factors associated with poor outcomes. Furthermore, we determined the cutoff value of duration of CPR in predicting poor neurologic outcomes and in-hospital mortality in patients caused by in-PICU CA as 17 and 23.5 min respectively.